Walt Hunter. Forms of a World: Contemporary Poetry and the Making of Globalization. Fordham UP, 2019. - Jeremy Glazier (Studies in 20th & 21st Century Literature, 2020)
Review of Walt Hunter Forms of a World: Contemporary Poetry and the Making of Globalization. Fordham UP, 2019. 190 pp.
Keywords: contemporary; poetry; criticism; globalization; Claudia Rankine